The Current Landscape of mRNA Vaccines Against Viruses and Cancer–A Mini Review - Ladak, Reese Jalal; He, Alexander J.; Huang, Yu-Hsun; Ding, Yu (Frontiers in Immunology, 2022)
Both infectious viral diseases and cancer have historically been some of the most common causes of death worldwide. The COVID-19 pandemic is a decidedly relevant example of the former. Despite progress having been made over past decades, new and improved techniques are still needed to address the limitations faced by current treatment standards, with mRNA-based therapy emerging as a promising solution. Highly flexible, scalable and cost-effective, mRNA therapy is proving to be a compelling vaccine platform against viruses. Likewise, mRNA vaccines show similar promise against cancer as a platform capable of encoding multiple antigens for a diverse array of cancers, including those that are patient specific as a novel form of personalized medicine. In this review, the molecular mechanisms, biotechnological aspects, and clinical developments of mRNA vaccines against viral infections and cancer will be discussed to provide an informative update of the current state of mRNA therapy research.